2007
DOI: 10.1073/pnas.0704866104
|View full text |Cite
|
Sign up to set email alerts
|

The plant signal salicylic acid shuts down expression of the vir regulon and activates quormone-quenching genes in Agrobacterium

Abstract: Agrobacterium tumefaciens is capable of transferring and integrating an oncogenic T-DNA (transferred DNA) from its tumor-inducing (Ti) plasmid into dicotyledonous plants. This transfer requires that the virulence genes (vir regulon) be induced by plant signals such as acetosyringone in an acidic environment. Salicylic acid (SA) is a key signal molecule in regulating plant defense against pathogens. However, how SA influences Agrobacterium and its interactions with plants is poorly understood. Here we show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
162
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(175 citation statements)
references
References 42 publications
(62 reference statements)
9
162
1
1
Order By: Relevance
“…Instead, SA may exert a direct effect on the Agrobacterium's virulence machinery. This was also supported by our findings and those of others (Yuan et al, 2007) that mutant plants with low SA levels promote, whereas those with high SA levels inhibit, tumor growth ( Figure 7A). Furthermore, constitutively high levels of SA and PR gene expression interfered with the expression of oncogenes, since the cpr5 mutant expressed only very low numbers of ipt transcripts at 6 d postinoculation compared with wild-type plants (Figure 8).…”
Section: Auxin and Et Are Involved In The Initiation Of Infection Witsupporting
confidence: 81%
See 2 more Smart Citations
“…Instead, SA may exert a direct effect on the Agrobacterium's virulence machinery. This was also supported by our findings and those of others (Yuan et al, 2007) that mutant plants with low SA levels promote, whereas those with high SA levels inhibit, tumor growth ( Figure 7A). Furthermore, constitutively high levels of SA and PR gene expression interfered with the expression of oncogenes, since the cpr5 mutant expressed only very low numbers of ipt transcripts at 6 d postinoculation compared with wild-type plants (Figure 8).…”
Section: Auxin and Et Are Involved In The Initiation Of Infection Witsupporting
confidence: 81%
“…The elevated auxin levels at 6 d postinoculation and in tumors may promote agrobacteria invasion by suppression of SA-mediated host defenses. Recently it has been shown that SA has an inhibitory effect on virulence of agrobacteria (Yuan et al, 2007;Anand et al, 2008). SA directly inhibits the expression of the vir regulon of the Ti plasmid that is essential for the transfer and integration of the T-DNA into the host genome.…”
Section: Auxin and Et Are Involved In The Initiation Of Infection Witmentioning
confidence: 99%
See 1 more Smart Citation
“…AttM appears to contribute to bacterial fitness within the plant tumor (63) and may also function in interkingdom signaling between the plant and the bacterium. Salicylic acid and the nonprotein amino acid GABA, both naturally found in plants, have been shown to induce attM expression (97)(98)(99), and overexpression of either of these compounds in plants increases the plant's resistance to A. tumefaciens infection (97,98). Additionally, proline, which is a competitive antagonist of GABA import into Agrobacterium, accumulates in plant gall tumors, where it may function to limit GABA-induced AHL degradation (100).…”
Section: Enzymatic Degradation and Inactivation Of Ahlsmentioning
confidence: 99%
“…This pair of TCSs can sense the presence of phenolic compounds released by wounded plants, thereby triggering the activation of several genes involved in tumor induction (Lin et al, 2008). Conversely, (2H)-1,4-benzoxazin-3(4H)-one (BOA) and salicylic acid (SA), two plant phenolic compounds, can inhibit A. tumefaciens infection by blocking the expression of VirA/VirG (Zhang et al, 2000;Yuan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%